THE SHIFTS OF FUNCTIONAL WORDS IN THE TRANSLATION OF TOERâS BUMI MANUSIA INTO ENGLISH BY MAX LANE - Rahmawatie, Inge; Engliana, Engliana; Miranti, Ira (Language Circle: Journal of Language and Literature, 2017)
In the process of translation, the translator uses class shift as a translation strategy to achieve a communicative translation. The aims of the research are to investigatehow functional word shifts performed and kinds of classshift in the novel. This research paper was conducted by using the qualitative method. The result of the research indicated that there were 12 types of classshift found on the selected pages in the novel. In this research, the writer found 177classshifts in translation. There were shift from adverb to noun (3 data) is 1,7 %, shift from noun to adverb (4 data) is2,26 %, shift from adjective to verb (7 data) is 3,96 %, shift from adjective to noun (8 data) is 4,52 %, shift from adverb to adjective (9 data) is 5,09 %, shift from verb to adverb (10 data) is 5,65 %, shift from noun to adjective (11 data) is 6,21 %, shift from adverb to verb (15 data) is 8,47 %, shift from noun to verb (22 data) is 12,43 %, shift from verb to adjective (23 data) is 12,99 %, shift from verb to noun (26 data) is 14,69 %, and shift from adjective to adverb (39 data) is 22,03 %. Based on the elaborations above, it can be concluded that the result of this research show the translation of functional word shift are considered to be accurate, clear and natural because the words in TL has the same message with the words in SL although they have different classes of the word.Â